X-Git-Url: http://lambda.jimpryor.net/git/gitweb.cgi?p=lambda.git;a=blobdiff_plain;f=week4.mdwn;h=58d6bc38204bd3bcbf4afabe6d9c4306b82735de;hp=06581f01518648d75c077a4e18de89c1647d1a38;hb=HEAD;hpb=276c8f5fcba4ed0b79225eece8fb3f269e98c385 diff --git a/week4.mdwn b/week4.mdwn deleted file mode 100644 index 06581f01..00000000 --- a/week4.mdwn +++ /dev/null @@ -1,161 +0,0 @@ -[[!toc]] - -#These notes return to the topic of fixed point combiantors for one more return to the topic of fixed point combinators# - -Q: How do you know that every term in the untyped lambda calculus has -a fixed point? - -A: That's easy: let `T` be an arbitrary term in the lambda calculus. If -`T` has a fixed point, then there exists some `X` such that `X <~~> -TX` (that's what it means to *have* a fixed point). - -
-let W = \x.T(xx) in
-let X = WW in
-X = WW = (\x.T(xx))W = T(WW) = TX
-
- -Q: How do you know that for any term T, YT is a fixed point of T? - -A: Note that in the proof given in the previous answer, we chose `T` -and then set `X = WW = (\x.T(xx))(\x.T(xx))`. If we abstract over -`T`, we get the Y combinator, `\T.(\x.T(xx))(\x.T(xx))`. No matter -what argument `T` we feed Y, it returns some `X` that is a fixed point -of `T`, by the reasoning in the previous answer. - -Q: So if every term has a fixed point, even Y has fixed point. - -A: Right: - - let Y = \T.(\x.T(xx))(\x.T(xx)) in - Y Y = \T.(\x.T(xx))(\x.T(xx)) Y - = (\x.Y(xx))(\x.Y(xx)) - = Y((\x.Y(xx))(\x.Y(xx))) - = Y(Y((\x.Y(xx))(\x.Y(xx)))) - = Y(Y(Y(...(Y(YY))...))) - -Q: Ouch! Stop hurting my brain. - -A: Let's come at it from the direction of arithmetic. Recall that we -claimed that even `succ`---the function that added one to any -number---had a fixed point. How could there be an X such that X = X+1? -Then - - X = succ X = succ (succ X) = succ (succ (succ (X))) = succ (... (succ X)...) - -In other words, the fixed point of `succ` is a term that is its own -successor. Let's just check that `X = succ X`: - - let succ = \n s z. s (n s z) in - let X = (\x.succ(xx))(\x.succ(xx)) in - succ X - = succ ((\x.succ(xx))(\x.succ(xx))) - = succ (succ ((\x.succ(xx))(\x.succ(xx)))) - = succ (succ X) - -You should see the close similarity with YY here. - -Q. So `Y` applied to `succ` returns infinity! - -A. Yes! Let's see why it makes sense to think of `Y succ` as a Church -numeral: - - [same definitions] - succ X - = (\n s z. s (n s z)) X - = \s z. s (X s z) - = succ (\s z. s (X s z)) ; using fixed-point reasoning - = \s z. s ([succ (\s z. s (X s z))] s z) - = \s z. s ([\s z. s ([succ (\s z. s (X s z))] s z)] s z) - = \s z. s (s (succ (\s z. s (X s z)))) - -So `succ X` looks like a numeral: it takes two arguments, `s` and `z`, -and returns a sequence of nested applications of `s`... - -You should be able to prove that `add 2 (Y succ) <~~> Y succ`, -likewise for `mult`, `minus`, `pow`. What happens if we try `minus (Y -succ)(Y succ)`? What would you expect infinity minus infinity to be? -(Hint: choose your evaluation strategy so that you add two `s`s to the -first number for every `s` that you add to the second number.) - -This is amazing, by the way: we're proving things about a term that -represents arithmetic infinity. It's important to bear in mind the -simplest term in question is not infinite: - - Y succ = (\f.(\x.f(xx))(\x.f(xx)))(\n s z. s (n s z)) - -The way that infinity enters into the picture is that this term has -no normal form: no matter how many times we perform beta reduction, -there will always be an opportunity for more beta reduction. (Lather, -rinse, repeat!) - -Q. That reminds me, what about [[evaluation order]]? - -A. For a recursive function that has a well-behaved base case, such as -the factorial function, evaluation order is crucial. In the following -computation, we will arrive at a normal form. Watch for the moment at -which we have to make a choice about which beta reduction to perform -next: one choice leads to a normal form, the other choice leads to -endless reduction: - - let prefac = \f n. isZero n 1 (mult n (f (pred n))) in - let fac = Y prefac in - fac 2 - = [(\f.(\x.f(xx))(\x.f(xx))) prefac] 2 - = [(\x.prefac(xx))(\x.prefac(xx))] 2 - = [prefac((\x.prefac(xx))(\x.prefac(xx)))] 2 - = [prefac(prefac((\x.prefac(xx))(\x.prefac(xx))))] 2 - = [(\f n. isZero n 1 (mult n (f (pred n)))) - (prefac((\x.prefac(xx))(\x.prefac(xx))))] 2 - = [\n. isZero n 1 (mult n ([prefac((\x.prefac(xx))(\x.prefac(xx)))] (pred n)))] 2 - = isZero 2 1 (mult 2 ([prefac((\x.prefac(xx))(\x.prefac(xx)))] (pred 2))) - = mult 2 ([prefac((\x.prefac(xx))(\x.prefac(xx)))] 1) - ... - = mult 2 (mult 1 ([prefac((\x.prefac(xx))(\x.prefac(xx)))] 0)) - = mult 2 (mult 1 (isZero 0 1 ([prefac((\x.prefac(xx))(\x.prefac(xx)))] (pred 0)))) - = mult 2 (mult 1 1) - = mult 2 1 - = 2 - -The crucial step is the third from the last. We have our choice of -either evaluating the test `isZero 0 1 ...`, which evaluates to `1`, -or we can evaluate the `Y` pump, `(\x.prefac(xx))(\x.prefac(xx))`, to -produce another copy of `prefac`. If we postpone evaluting the -`isZero` test, we'll pump out copy after copy of `prefac`, and never -realize that we've bottomed out in the recursion. But if we adopt a -leftmost/call by name/normal order evaluation strategy, we'll always -start with the isZero predicate, and only produce a fresh copy of -`prefac` if we are forced to. - -Q. You claimed that the Ackerman function couldn't be implemented -using our primitive recursion techniques (such as the techniques that -allow us to define addition and multiplication). But you haven't -shown that it is possible to define the Ackerman function using full -recursion. - -A. OK: - -
-A(m,n) =
-    | when m == 0 -> n + 1
-    | else when n == 0 -> A(m-1,1)
-    | else -> A(m-1, A(m,n-1))
-
-let A = Y (\A m n. isZero m (succ n) (isZero n (A (pred m) 1) (A (pred m) (A m (pred n))))) in
-
- -For instance, - - A 1 2 - = A 0 (A 1 1) - = A 0 (A 0 (A 1 0)) - = A 0 (A 0 (A 0 1)) - = A 0 (A 0 2) - = A 0 3 - = 4 - -A 1 x is to A 0 x as addition is to the successor function; -A 2 x is to A 1 x as multiplication is to addition; -A 3 x is to A 2 x as exponentiation is to multiplication--- -so A 4 x is to A 3 x as super-exponentiation is to exponentiation... -